A Study on Employee Morale and Quality of Work Life Author(s):J.Vignesh Shankar - Shankar, J.Vignesh (International Journal of Scientific Research and Management (IJSRM), 2016)
The main purpose of this paper is to investigate and determine the qua lity of work life and morale ofemployees and their effects on organizational operations. To reach the quality of work life mostly dependsupon making regular attempts from an organization, which provides their employees with moreopportunities so that they can be more effective in their organization. Quality in an organization is definedas an advantage, as a value, as determination of conformity and as meeting customer’s expectations. Goodquality of work life is necessary for an organization to attract and to retain skilled and talented employees.Employees are the most important assets of any organizations and its success or failure depends on theirqualifications and performance. In order to survive in the competitive market because of Liberalization,Privatization and Globalization and to minimize the attrition rate of employees the quality of work lifeinitiatives are very important. Motivated employees and Satisfied customers are the backbone of anysuccessful organizations. This paper focuses and analyzes the literature findings which involve quality ofwork life and predictors of employee motivational strategies.